Diagnostic Accuracy of Circular RNAs in Different Types of Samples for Detecting Hepatocellular Carcinoma: A Meta-Analysis - Nie, Guilin; Peng, Dingzhong; Li, Bei; Lu, Jiong; Xiong, Xianze (Frontiers in Genetics, 2021)
The lack of accurate biomarkers impeded the screening, diagnosis and early treatment of hepatocellular carcinoma (HCC). As a result of the development of high-throughput transcriptome analysis techniques, circular RNAs, a newly discovered class of noncoding RNAs, were recognized as potential novel biomarkers. This meta-analysis was performed to update the diagnostic roles of circular RNAs for HCC. We acquired 23 articles from PubMed, Web of Science, EMBASE, and Cochrane Library databases up to September 2021. The overall sensitivity was 0.80 (95% CI: 0.77-0.84), and the specificity was 0.83 (95% CI: 0.79-0.85), with an AUC of 0.88 (0.85-0.91). Considering of the significant heterogeneity, studies were divided into four groups based on the control types. The circular RNAs in exosomes had a sensitivity of 0.69 (95% CI: 0.61-0.75), and a highest specificity of 0.91 (95% CI: 0.83-0.96). The pooled sensitivity of circular RNAs in serum/plasma was 0.84 (95% CI: 0.81-0.87), and the pooled specificity was 0.83 (95% CI: 0.79-0.86). The pooled sensitivity of circular RNAs distinguishing tumor tissue from chronic hepatitis/cirrhosis tissues was 0.56 (95% CI: 0.48-0.64), and specificity was 0.76 (95% CI: 0.67-0.82). When the controls were adjacent tissues, the sensitivity was 0.78 (95% CI: 0.70-0.84), and the specificity was 0.78 (95% CI: 0.71-0.85). Hsa_circ_0001445 with a pooled sensitivity of 0.81, a specificity of 0.76 and an AUC of 0.85 in two studies, might be a suitable diagnostic blood biomarker for HCC. Relying on function in HCC, the AUC of subgroups were 0.88 (95%CI: 0.84-0.90) (function group) and 0.87 (95%CI: 0.84-0.90) (unknown function group). As for only reported in HCC or not, these circular RNAs had an AUC of 0.89 (95%CI: 0.86-0.91) (only in HCC) and 0.85 (95%CI: 0.82-0.88) (not only in HCC). In conclusion, the results suggested that circular RNAs were acceptable biomarkers for detecting HCC, especially those circular RNAs existing in exosomes or serum/plasma.